Clinical application of virtual reality in patients with cardiovascular disease: state of the art - Micheluzzi, Valentina; Navarese, Eliano Pio; Merella, Pierluigi; Talanas, Giuseppe; Viola, Graziana; Bandino, Stefano; Idini, Chiara; Burrai, Francesco; Casu, Gavino (Frontiers in Cardiovascular Medicine, 2024)
Virtual reality offers a multisensory experience to patients, allowing them to hear, watch, and interact in a virtual environment. Immersive virtual reality is particularly suitable for the purpose of completely isolating patients from the external environment to remove them from the suffering related to the disease. In this state of the art, we summarise the available literature on the effectiveness of virtual reality on various physical and psychological outcomes in patients with atherosclerotic cardiovascular disease. Virtual reality has been employed in the cardiovascular field in various settings such as cardiac rehabilitation, interventional cardiology, and cardiac surgery.This technology offers promising opportunities to improve several outcomes related to cardiovascular disease, but further research is needed to entirely capture its benefits and to standardize the intervention.